Next Generation Entrepreneurship - Erkut, Burak; Esenyel, Vildan (IntechOpen, 2022)
The book deals with next-generation entrepreneurship and aims to answer the questions of in which ways, how, through which focal directions, and by which means will next-generation entrepreneurship emerge and shape the market processes. Under this broad overview, the book is sub-divided into three sections: "Entrepreneurship Education and Young Perspectives", "New Challenges for Entrepreneurship", and "Shaping the Next Generation of Entrepreneurship". The book balances empirical evidence with conceptual contributions.